2019
DOI: 10.3889/oamjms.2019.199
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians' Awareness of Autism Spectrum Disorder: Results from a Survey Study

Abstract: AIM: Autism spectrum disorder (ASD) is a common neurodevelopmental disorder in children. Family physicians with the first medical contact of children are among the most frequent physicians with ASD. We aimed to investigate family physicians' awareness of ASD. METHODS: This study was carried out family physicians in between September 25-October 15, 2018. The questionnaire form on autism awareness prepared by the researcher was delivered to family physicians electronically and in printed form, and it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Thirteen studies assessed GP knowledge of autism. Two studies (Campbell, 2008; Unigwe et al., 2017) used an adapted version of the ASK (Stone, 1987), two studies (Eseigbe et al., 2015; Hend, 2017) used the KCAHW (Bakare et al., 2008), and the remainder (k = 8) used a bespoke assessment developed by the research team (Altay, 2019; Berenstein, 2012; Eray & Murat, 2017; Garg, Lillystone, Dossetor, Kefford, & Chong, 2014; Kirby, Davies, & Bryant, 2005; Lian, Ho, Yeo, & Ho, 2003; Martínez, Tadeo, Montero, & Antonio, 2013; Rahbar, Ibrahim, & Assassi, 2011). In one study (Muhammad, Dhia Al‐Deen, & Abdul Muhsin, 2013) the authors cite Heidgerken, Geffken, Modi, and Frakey (2005) in the method, and yet the results reflect the structure of the KCHAW (Bakare et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies assessed GP knowledge of autism. Two studies (Campbell, 2008; Unigwe et al., 2017) used an adapted version of the ASK (Stone, 1987), two studies (Eseigbe et al., 2015; Hend, 2017) used the KCAHW (Bakare et al., 2008), and the remainder (k = 8) used a bespoke assessment developed by the research team (Altay, 2019; Berenstein, 2012; Eray & Murat, 2017; Garg, Lillystone, Dossetor, Kefford, & Chong, 2014; Kirby, Davies, & Bryant, 2005; Lian, Ho, Yeo, & Ho, 2003; Martínez, Tadeo, Montero, & Antonio, 2013; Rahbar, Ibrahim, & Assassi, 2011). In one study (Muhammad, Dhia Al‐Deen, & Abdul Muhsin, 2013) the authors cite Heidgerken, Geffken, Modi, and Frakey (2005) in the method, and yet the results reflect the structure of the KCHAW (Bakare et al., 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It is important that family physicians refer patients with ADHD symptoms and those with learning difficulties to the children and adolescent psychiatry. It is important in this respect that primary care physicians are subject to current education programs on ADHD and other mental disorders as suggested by previous studies (39). It should be known that ADHD is a disorder frequently associated with other psychiatric disorders and cases should be handled in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…A further 11.5% of GPs endorsed "singing" and "irritability" as diagnostic features of autism. In closing, Altay (69) argued that GP knowledge of these conditions was not satisfactory. Echoing the recommendations of others, Altay called for an increase in autism training programmes for GPs, with a particular focus on clinical features, comorbid conditions, and recent aetiological evidence.…”
Section: Quantitative Findings Knowledgementioning
confidence: 99%
“…These GPs speculated that the child may be socially withdrawn, have a preference or interest in one item or toy, have difficulty with following instructions, have limited if any language, and may also have cognitive difficulties. Meanwhile in Altay (69), nearly a quarter of GPs indicated that 'learning disability' was a diagnostic marker for autism. These findings were buttressed by another Turkish study (74) which reported that prior to an educational intervention, 23.3% of GPs agreed that autism is "always" accompanied by a learning disability, while 12% were unsure.…”
Section: -End Of the Spectrummentioning
confidence: 99%
See 1 more Smart Citation